DYNAMIC SIMULATION OF DISTILLATION COLUMN UNIT TO STUDY OPERATIONAL FAILURES - Ramzan, N.; Naveed, S.; Faheem, M.; Feroze, N.; Witt, W. (The Nucleus, 2020)
Distillation column units present special safety hazards because of their large inventories, which often involve flammable solvents. Thus study of operational failures, which may results into incidents or accidents, in a distillation column unit by simulation is of value. In such cases, a mandatory condition in safety assessment is the detailed disturbance analysis through simulation to cover a wide range of operation. In this paper, scenarios such as loss of cooling, more or less steam flow rate, high or low feed flow rate etc. are simulated to evaluate control structures and for safety examination. This is achieved through introduction of small and large disturbances. The distillation column unit, which is part of a hydrocarbon recovery plant, from a real chemical plant is taken for case study. The operational failures in distillation column unit under study were identified through simulation with two different inferential configurations and a dual composition control scheme. Simulation results illustrates that the condenser level controller, sump level controller, temperature controller and vent to atmosphere keeps the process controlled variables at the set point for these disturbances except for the case where 20% reduction in feed was introduced.